2016
DOI: 10.1111/aos.13195
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between a dissociated optic nerve fibre layer appearance after macular hole surgery and Muller cell debris on peeled internal limiting membrane

Abstract: The extent of DONFL observed postoperatively can be partly explained by the amount of retinal side cellular debris on the retinal side of the peeled ILM. Surgical strategies which minimize this material could reduce the extent of DONFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…The ILM is characterized by a smooth vitreal side and an undulated retinal side, and the retinal side is found with Müller cell debris on removed ILM specimens. 16 Therefore, the retinal side of the ILM, if it is to cover the MH, would theoretically provide a more favorable structure for glia proliferation and macular closure. We found that 38 of the 40 patients achieved anatomical reduction of MH successfully — 95%.…”
Section: Discussionmentioning
confidence: 99%
“…The ILM is characterized by a smooth vitreal side and an undulated retinal side, and the retinal side is found with Müller cell debris on removed ILM specimens. 16 Therefore, the retinal side of the ILM, if it is to cover the MH, would theoretically provide a more favorable structure for glia proliferation and macular closure. We found that 38 of the 40 patients achieved anatomical reduction of MH successfully — 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Gelman et al [13] have reviewed some retinal damage induced by ILM removal including damage to müller cell, dissociated optic nerve fiber layer, and phototoxic damage. A number of studies have also investigated the histopathological characteristic of ILM [14,15]. The ILM is characterized by a smooth vitreal side and an undulated retinal side, and the retinal side is found with müller cell debris on removed ILM specimens.…”
Section: Discussionmentioning
confidence: 99%
“…These are commonest nasally and thought to represent traction on Muller cells which surround capillaries within the superficial retinal layers ( Figure 2). 40…”
Section: A) Immediatementioning
confidence: 99%
“…It is unclear if it has functional consequences, with some authors reporting defects in microperimetry and reduced macular sensitivity linked to the areas most affected by DONFL. 40,43,44 A transient increase in RNFL thickness in the area of peeled ILM may occur postoperatively.…”
Section: B) Inner Retinal Changes Observed On Retinal Imagingmentioning
confidence: 99%